2005
DOI: 10.1007/s10517-005-0398-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Opioid Antagonist Naloxone on Maternal Motivation in Albino Rats

Abstract: We studied the effect of nonselective antagonist of opioid receptor naloxone on the behavior of albino female rats on days 4-6 after delivery. Intraperitoneal injection of naloxone (5 mg/kg) significantly stimulated maternal reactions (increased the number of approaches to pups, decreased the latency of their transfer into new location). Intranasal naloxone (1 mg/kg) produced similar changes. Naloxone in intraperitoneal dose of 1 mg/kg and intranasal dose of 0.2 mg/kg virtually did not modify maternal behavior. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…1). Our results, along with our previous data [2,3] create the basis for the development of methods for correction (stimulation or attenuation) of the level of maternal motivation in clinical practice.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…1). Our results, along with our previous data [2,3] create the basis for the development of methods for correction (stimulation or attenuation) of the level of maternal motivation in clinical practice.…”
Section: Resultssupporting
confidence: 60%
“…In two series D1/D2 antagonist was injected, in two other series haloperidol injection was preceded by a threshold intranasal naloxone dose (0.2 mg/kg). Our previous studies [2] showed that this dose of naloxone had a negligible effect on the intensity of maternal reactions (in contrast to, e.g., 1 mg/kg).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…When used with carefully selected medications, this delivery route has the advantage of rapid onset, high plasma bioavailability, direct transport to the central nervous system across the olfactory mucosa, elimination of first pass metabolism and, perhaps most importantly, elimination of the use of needles [713]. …”
Section: Introductionmentioning
confidence: 99%